Understanding the structural foundation of mucroporin peptide as a potential anti-COVID-19 candidate: Computational methods - Fakih, Taufik Muhammad; Ramadhan, Dwi Syah Fitra; Rizkita, Aden Dhana (Biogenesis: Jurnal Ilmiah Biologi, 2023)
.